2018
DOI: 10.1016/j.bjoms.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Neurosensory recovery after trauma to the orbital floor: a prospective trial with dexamethasone

Abstract: Our aims were to document the occurrence of neurosensory disturbances of the infraorbital nerve six months after operation for an orbital blow-out fracture, and to find out whether dexamethasone facilitates neurosensory regeneration. Patients were randomly assigned to one of two groups: the study group was given a total of dexamethasone 30mg, whereas the control group were given neither glucocorticoid nor placebo. Each patient's infraorbital neurosensory state was recorded preoperatively, immediately postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Evidence-Based Medicine: Trials have demonstrated a negligible effect of perioperative steroids on postoperative nausea and vomiting 25 ( Level of Evidence: I ), infraorbital sensory recovery 26 ( Level of Evidence: II ), and wound healing 27 ( Level of Evidence: III ), but have demonstrated a significant reduction in edema following orbital exploration 28 ( Level of Evidence: II ). However, literature evaluating the effect of steroids on infection rates is lacking.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence-Based Medicine: Trials have demonstrated a negligible effect of perioperative steroids on postoperative nausea and vomiting 25 ( Level of Evidence: I ), infraorbital sensory recovery 26 ( Level of Evidence: II ), and wound healing 27 ( Level of Evidence: III ), but have demonstrated a significant reduction in edema following orbital exploration 28 ( Level of Evidence: II ). However, literature evaluating the effect of steroids on infection rates is lacking.…”
Section: Resultsmentioning
confidence: 99%
“…The complications reported in the literature, for example, in orbital blow-out fractures have been diplopia, infraorbital nerve injury, and esthetics which are fortunately often transient but affect the quality of life severely [21]. One of the factors proven to diminish long-lasting neurosensory disturbance has been short delay (<1 week) to surgical intervention when surgery is clinically indicated [22]. Indeed, the current study revealed that a delay-related cause was by far the most common cause of malpractice complaint (63.2%), compared with other causes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may find relief from congestion through the use of nasal decongestant sprays, and if systemic steroids are available, they may be used to decrease orbital edema. 39,40 Beyond this basic medical management, emergent evacuation is recommended if signs of ocular muscle entrapment, traumatic vision loss, or suspected globe rupture are present.…”
Section: Orbital Fracturesmentioning
confidence: 99%